Screening of Dahlia pinnata for its Antimicrobial Activity - Sharad Bissa; Bohra, Avinash; A, Bohra (Journal of Research in Biology, 2011)
The demand for more and more drugs from plant sources is continuously increasing. The present study deals with the antibacterial activity of different plant part (Root, stem, leaf and flowers) extracts of Dahlia pinnata. The antibacterial activ-ity of both fresh and dried plant parts were determined in aqueous, alcohol, chloro-form and petroleum ether extracts using agar disc diffusion method against E.coli, Salmonella typhi, Klebsiella pneumoniae, Enterobacter aerogenes and Agrobacterium tumefaciens. Dahlia pinnata possessed highest antibacterial activity in its chloroform extract of dried leaves against Enterobacter aerogenes